Effects of different shoe-lacing patterns on dorsal pressure distribution during running and perceived comfort - Hagen, M.; Hömme, A.-K.; Umlauf, T.; Hennig, E. M. (Research in Sports Medicine, 2010)
The purpose of this study was to investigate the effects of four lacing patterns (one regular, one tight, and two seven-eyelet lacings) on dorsal foot pressures during running and the perception of comfort and stability with 14 male rearfoot runners. By using a pressure insole, peak dorsal pressures were measured under the shoe's tongue. Highest peak pressures were found above the talus, the navicular bone, and the first ray. Seven-eyelet lacings showed a significant enhancement of perceived stability without differences in perceived comfort compared with a regular six-eyelet technique. Reduction of pressure on the talus, the navicular bone, and the extensor tendons is related to better comfort. With individually chosen special seven-eyelet lacings runners can improve foot-shoe coupling without increasing peak dorsal pressures on the tarsus. Knowledge of the location of the dorsal pressure distribution is useful for new tongue and lacing constructions to improve comfort in running shoes while maintaining stability.